Pengembangan Media Digital Berbasis Kearifan Lokal Terhadap Kemampuan Matematika Permulaan Anak Usia 5-6 Tahun di TK Negeri Pembina Sekayu - Ningsih, Ayu Wahyu; Dewi, Kurnia; Handayani, Tutut; Febriyanti, Febriyanti; Oktamarina, Lidia (LP. Ma'arif Janggan Magetan, 2024)
The purpose of this study was to develop learning media in the form of digital media that are valid, practical, and effective in improving the ability to introduce mathematics to children aged 5-6 years. The method used is Research and Development with the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were group B at TK Negeri Pembina Sekayu. Data collection techniques used validity tests, practicality tests, and effectiveness tests. Validity, practicality, and effectiveness data were obtained based on questionnaire response data analyzed using a Likert scale. The results of the study showed the validity of material experts 93, very valid category, media design experts 93 very valid categories, and language experts 84 very valid categories. The practicality test of the Digital media initial field trial 70.205 practical, the main field trial 90.36 very practical, and the teacher response questionnaire 90 very practical category. The results of the study showed the effectiveness test by conducting a pretest before use 46% and the Posttest results 95% effective category. The effectiveness test of digital media based on local wisdom can be seen in the t-test so that the calculated t = (8.516) is obtained while for the t table = (0.443). then it can be concluded that the calculated t> t table then Ha is accepted and H0 is rejected, which means that there is a significant influence of the use of digital media based on local wisdom on the initial mathematical abilities of children aged 5-6 years at Pembina Sekayu State Kindergarten. The results of this study conclude that digital media based on local wisdom to recognize mathematical abilities is declared valid, practical, and effective for use in learning.